In-nozzle flow and spray characteristics for mineral diesel, Karanja, and Jatropha biodiesels. (15th October 2015) - Agarwal, Avinash Kumar; Som, Sibendu; Shukla, Pravesh Chandra; Goyal, Harsh; Longman, Douglas
Highlights: In-nozzle flow characterization for biodiesel sprays. Comparison of experimental spray parameters and nozzle hole simulations. Effect of Karanja and Jatropha biodiesel on in-nozzle cavitation. Cavitation formation investigation with diesel and biodiesels. Nozzle hole outlet fuel velocity profile determination for test fuels. Abstract: Superior spray behavior of fuels in internal combustion engines lead to improved combustion and emission characteristics therefore it is necessary to investigate fuel spray behavior of new alternative fuels. This study discusses the evolution of the in-nozzle orifice parameters of a numerical simulation and the evolution of spray parameters of fuel spray in a constant-volume spray chamber during an experiment. This study compares mineral diesel, biodiesels (Karanja-and Jatropha-based), and their blends with mineral diesel. The results show that mineral diesel provides superior atomization and evaporation behavior compared to the biodiesel test fuels. Karanja biodiesel provides superior atomization and evaporation characteristics compared to Jatropha biodiesel. The qualitative comparison of simulation and experimental results in tandem shows that nozzle-hole design is a critical parameter for obtaining optimum spray behavior in the engine combustion chamber.